IMPLEMENTASI SISTEM INFORMASI DESA DALAM PENGELOLAAN DANA DESA - Jaharuddin, Irwana; Muhammadiah, Muhammadiah; Yahya, Muhammad (Universitas Muhammadiyah Makassar, 2025)
This research aims to find out how the village information system is implemented in managing village funds in Pakatto Village, Bontomarannu District, Gowa Regency in terms of human resources, hardware, software, data and networks. The type and type of research used is descriptive qualitative, where information is obtained through observation, interviews and documentation. The informants in this research were the Pakatto Village Head, Pakatto Village Secretary, Pakatto Village Office Staff and Pakatto Village Community. This research uses Agus Mulyanto's information system components, namely human resources, hardware, software, data and networks. The research results show that the ability of human resources to operate the system is still lacking and software errors often occur in the system.